Method for modifying titanium-based porous transmission layer by using supercritical fluid technology
By using supercritical fluid technology to deposit precious metal films on titanium fibers and sintered with water-soluble vinylon fibers, the problem of oxidation of titanium-based porous transport layer during sintering is solved, and the lower resistance of titanium fiber felt is achieved and stronger oxidation resistance.
Patent Information
- Application Number
- CN202411583501.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing titanium-based porous transport layer is easily oxidized during the sintering process, resulting in an increase in the resistance of the electrolytic cell, reducing the performance of the electrolytic cell, and poor binding force of the coating, making it easy to fall off.
采用超临界流体技术改性钛基多孔传输层,通过在钛纤维上沉积贵金属薄膜,结合水溶性维纶纤维进行混合和烧结,形成具有更均匀镀层、更强结合力和更低电阻率的钛纤维毡。
The titanium fiber felt has a lower resistivity and more oxidation resistance, uniform thickness of the coating, strong binding force, and is not easy to fall off, improving the performance and stability of the electrolytic cell.
Smart Images

Figure CN119465216A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry and relates to a method for modifying a titanium-based porous transmission layer by utilizing supercritical fluid technology. Background Art
[0002] The PEM electrolyzer is mainly composed of end plates, bipolar plates, diffusion layers, catalyst layers, proton exchange membranes and gaskets. Among them, the anode porous transmission layer is mainly composed of titanium mesh, titanium particle sintered plate, titanium fiber sintered felt and other structures. At present, the titanium fiber sintered felt, referred to as titanium felt, is mostly used in the PEM electrolysis water market at home and abroad. The main processing technology includes titanium fiber drawing, pressing sintering and surface treatment. Most of the fibers used in titanium fiber felt are made by cutting or drawing. After being prepared into titanium felt, titanium oxide is easily generated during the operation of the electrolytic cell, which increases the resistance of the electrolytic cell and reduces the performance of the electrolytic cell. For this reason, most of the current titanium-based porous transmission layers are further applied with a protective coating on the surface by chemical plating or electroplating after the titanium fiber felt is sintered and formed. However, since the titanium fiber felt is easily oxidized during the sintering process, if it is not properly handled during the chemical plating or electroplating process, the coating has poor bonding strength and is easy to fall off.
[0003] Supercritical fluid refers to a fluid in a special state formed when its temperature and pressure are both above the critical point. It has the advantages of low viscosity, controllable density, large diffusion coefficient, zero surface tension, good fluidity and permeability, and excellent transfer characteristics. Therefore, it has the characteristics that physical properties such as density, viscosity, dielectric constant, and diffusion coefficient are sensitive to changes in pressure and temperature. Supercritical fluid deposition usually refers to the high-purity thin film deposition process achieved by chemical reaction of soluble organic metal compounds on the surface of the substrate in a supercritical carbon dioxide environment.
[0004] In this process, hydrogen and metal precursors first diffuse and adsorb to the substrate surface, then react on its surface to generate pure metal and hydrogenated ligands, then desorb the hydrogenated ligands from the substrate surface and dissolve in supercritical carbon dioxide solution, leaving a pure metal film on the substrate surface. Compared with ordinary electrochemical deposition, due to the low surface tension and viscosity, high diffusion coefficient and other characteristics of supercritical fluid deposition, the prepared deposition layer has superior performance, and has the characteristics of room temperature, non-toxic, environmentally friendly, safe and easy to use, and high product quality in modified fiber processing. Summary of the invention
[0005] The purpose of the present invention is to provide a method for modifying a titanium-based porous transport layer using supercritical fluid technology. Compared with the coating obtained by other methods, the coating obtained by the present invention has a more uniform thickness, stronger bonding force, and is not easy to fall off. The prepared titanium fiber felt has a lower resistivity and is more resistant to oxidation.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The method for modifying a titanium-based porous transport layer using supercritical fluid technology comprises the following steps performed in sequence:
[0008] S11. Put the precursor of the precious metal into a supercritical device, put the titanium fiber at the bottom of the device, and introduce carbon dioxide gas into the sealed container at a gas flow rate of 220-520 mL / min. While keeping the carbon dioxide gas flowing, heat the supercritical device to a temperature of 200-400°C and a pressure of 15-18 MPa according to the program, so that the precursor of the precious metal and the carbon dioxide in the device reach a supercritical fluid state. Maintain magnetic stirring during the entire heating process at a stirring speed of 100-200 r / min to make the deposition more uniform, wherein the deposition time is 20-30 min. After the deposition is completed, the pressure is released to 5 MPa, and hydrogen is introduced at a gas flow rate of 500-700 mL / min. The temperature of the pressure release process is 300°C and the time is 2 h. After the pressure release is completed, titanium fiber modified by coating is obtained;
[0009] S12, the titanium fiber modified by plating and the water-soluble vinylon fiber are mixed in a mass ratio of (8-9): (1-2), and ultrasonically treated in deionized water for 3 hours until the dispersion is uniform, and then formed by a sheet forming machine to form a titanium fiber felt with uniform thickness, wherein the titanium fiber felt has a quantitative value of 50-400 g / m 2 ;
[0010] S13, the titanium fiber felt in step S12 is laminated and pressed, and then placed in a vacuum sintering furnace at 1000°C for 4 hours to remove impurities and part of the adhesive components in the production process, and the heat preservation time is 2 hours. Finally, the titanium fiber felt is rolled and flattened. The thickness of the prepared titanium fiber felt is 0.2-0.8 mm.
[0011] As a preferred technical solution of the present invention, in step S11, the precursor of the precious metal is one or more of ruthenium chloride trihydrate, [bis(2,2,6,6-tetramethyl-3,5-heptanedioate)(1,5-epoxydiene)ruthenium], and iridium acetylacetonate.
[0012] As a preferred technical solution of the present invention, in step S11, the diameter of the titanium fiber is 18-50 μm.
[0013] As a preferred technical solution of the present invention, in step S12, the diameter of the water-soluble vinylon fiber is 7 to 20 μm.
[0014] The method for modifying a titanium-based porous transport layer using supercritical fluid technology comprises the following steps performed in sequence:
[0015] S51. Mix titanium fiber and water-soluble vinylon fiber in a mass ratio of 8:2, put them into deionized water for 3 hours for ultrasonication until they are evenly dispersed, and then form them into titanium fiber felt with uniform thickness through a sheet forming machine. The obtained titanium fiber felt has a weight of 50 to 500 g / m 2 ;
[0016] S52, laminating and pressing the titanium fiber felt obtained in S51, and then sintering it in a vacuum sintering furnace at 1000° C. for 4 hours, keeping it warm for 2 hours, and finally rolling and leveling it. The thickness of the prepared titanium fiber felt is 0.23 to 0.90 mm;
[0017] S53, the titanium fiber felt in S52 is first cleaned with a methanol solution, then immersed in an oxalic acid solution with a mass fraction of 15-20% for 20 minutes, and then repeatedly rinsed with deionized water until the surface of the titanium fiber felt is neutral, and then dried to obtain a titanium fiber felt matrix to be deposited;
[0018] S54. Place the precious metal precursor into a supercritical device, place the titanium fiber felt substrate to be deposited at the bottom of the device, introduce carbon dioxide gas at a flow rate of 220-600 mL / min, heat the device to 200°C, and increase the pressure to 16-18 MPa, so that the precious metal precursor and carbon dioxide in the device reach a critical fluid state. The stirring speed is 100-180 r / min, and the deposition time is 20-30 min. Then, the device is depressurized to 5 MPa, and hydrogen is introduced at a flow rate of 500 mL / min for 2 h at 300°C to obtain a ruthenium-coated titanium fiber felt with a thickness of 0.25-0.93 mm.
[0019] As a preferred technical solution of the present invention, in step S51, the diameter of the titanium fiber is 18 to 50 μm, and the diameter of the water-soluble vinyl fiber is 15 to 20 μm.
[0020] As a preferred technical solution of the present invention, in step S54, the precursor of the precious metal is one or more of ruthenium chloride trihydrate, [bis(2,2,6,6-tetramethyl-3,5-heptanedioate)(1,5-epoxydiene)ruthenium], and iridium acetylacetonate.
[0021] Beneficial effects of the present invention:
[0022] (1) Using precious metal compounds as precursors and supercritical carbon dioxide as solvent, a precious metal film is prepared on titanium fiber through hydrogen catalytic reduction at a set temperature, pressure, and reaction time. Compared with traditional heat treatment methods, supercritical fluid technology requires a lower temperature, which helps to reduce energy consumption and the risk of substrate deformation. At the same time, supercritical fluid does not produce harmful substances during operation, reducing pollution to the environment. During the deposition process, due to the different sensitivity of the precursors used to the pressure increase rate, the pressure increase rate is regulated by adjusting the gas flow rate of carbon dioxide. When using ruthenium compounds in the present invention, the carbon dioxide gas flow rate is controlled at 220mL / min; in order to avoid defects in the structure of the coated metal film due to too fast a heating rate, which affects the quality of the deposited layer, the temperature is controlled at 200°C. After the deposition is completed, hydrogen is introduced to reduce the metal oxide with hydrogen to obtain a pure metal film, including the reduction of titanium fiber and the reduction of the coated metal.
[0023] (2) In the present invention, whether the titanium fiber is first coated with supercritical fluid technology and then sintered or sintered and then subjected to supercritical treatment, the electrochemical properties of the obtained titanium-based porous transmission layer are better, which shows that the advantages of the precious metal coating obtained using supercritical fluid technology are more obvious. Because there is no binding force between the titanium fibers in the wet-formed titanium fiber felt, the titanium fibers are formed by overlapping each other, and the felt strength is poor, so a small amount of water-soluble vinyl fiber is added to improve the strength of the felt. The residue of this part of the added water-soluble vinyl fiber can be removed by the vacuum sintering process in the subsequent steps, ensuring the purity of the precious metal coating.
[0024] (3) Using supercritical fluid technology to modify titanium fiber can achieve uniform and dense deposition of metal on the substrate, thereby obtaining a high-quality precious metal coating on the surface of titanium fiber, improving the corrosion resistance of titanium fiber, and then the modified titanium fiber is laid into a mesh, then pressed and flattened, and finally sintered to prepare titanium fiber felt, which can prevent titanium from being oxidized during the sintering process, reduce the oxygen content of the titanium fiber felt, and improve the conductivity of the titanium fiber felt; at the same time, the precious metal layer plated on the surface of the titanium fiber has catalytic activity, which can reduce the overall electrolytic cell catalyst loading. Compared with the coatings obtained by other methods, the coating deposited on the titanium fiber surface using supercritical fluid technology has a more uniform thickness, stronger bonding force, and is not easy to fall off. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0026] Figure 1 The resistivity curves of the anode gas transport layers prepared in the examples and comparative examples;
[0027] Figure 2Polarization curves of the anode gas transport layers prepared in the examples and comparative examples after assembling the electrolytic cell. DETAILED DESCRIPTION
[0028] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0029] Example 1
[0030] S1. Weigh 30 mg of ruthenium chloride trihydrate and 20 mg of iridium acetylacetonate respectively and put them into a supercritical device. Place a titanium fiber with a diameter of 20 μm at the bottom of the device. Pass carbon dioxide gas at a flow rate of 220 mL / min. Heat the device to 200°C and pressurize it to 15 MPa to make the precious metal precursor and carbon dioxide in the device reach a critical fluid state. The stirring speed is 100 r / min and the deposition time is 20 min. Then, depressurize the device to 5 MPa at 300°C and pass hydrogen gas at a flow rate of 500 mL / min for 2 h to obtain a titanium fiber modified by coating.
[0031] S2. The modified titanium fiber and the water-soluble vinylon fiber with a diameter of 15 μm were mixed at a mass ratio of 8:2, and ultrasonically dispersed in deionized water for 3 hours until uniformly dispersed. Then, the titanium fiber felt was formed by a sheet forming machine to form a titanium fiber felt with uniform thickness. The obtained titanium fiber felt had a quantitative weight of 100 g / m 2 ;
[0032] S3. Take 4 layers of titanium fiber felt prepared in S2, stack them neatly and press them, then put them into a 1000°C vacuum sintering furnace for 4 hours, keep them warm for 2 hours, and finally roll them flat. The thickness of the titanium fiber felt is 0.4 mm.
[0033] Example 2
[0034] S1. Weigh 30 mg of ruthenium chloride trihydrate and 20 mg of iridium acetylacetonate respectively and put them into a supercritical device. Place a titanium fiber with a diameter of 18 μm at the bottom of the device. Pass carbon dioxide gas at a flow rate of 320 mL / min. Heat the device to 300°C and pressurize it to 18 MPa to make the precious metal precursor and carbon dioxide in the device reach a critical fluid state. The stirring speed is 150 r / min and the deposition time is 23 min. Depressurize the device to 5 MPa at 300°C and pass hydrogen gas at a flow rate of 500 mL / min for 2 h to obtain a titanium fiber modified by coating.
[0035] S2. The modified titanium fiber and the water-soluble vinylon fiber with a diameter of 7 μm were mixed at a mass ratio of 9:1, and ultrasonically dispersed in deionized water for 3 hours until the dispersion was uniform. Then, the titanium fiber felt was formed by a sheet forming machine to form a titanium fiber felt with uniform thickness. The obtained titanium fiber felt had a weight of 50 g / m 2 ;
[0036] S3. Take 4 layers of titanium fiber felt prepared in S2, stack them neatly and press them, then put them into a 1000°C vacuum sintering furnace for 4 hours, keep them warm for 2 hours, and finally roll them flat. The thickness of the titanium fiber felt is 0.2 mm.
[0037] Example 3
[0038] S1. Weigh 50 mg of [bis(2,2,6,6-tetramethyl-3,5-heptanedicarboxylate)(1,5-epoxydiene)ruthenium] and 20 mg of iridium acetylacetonate and put them into a supercritical device. Place a titanium fiber with a diameter of 50 μm at the bottom of the device. Pass carbon dioxide gas at a flow rate of 520 mL / min. Heat the device to 400°C and pressurize it to 18 MPa to make the precious metal precursor and carbon dioxide in the device reach a critical fluid state. The stirring speed is 200 r / min and the deposition time is 30 min. Depressurize the device to 5 MPa at 300°C and pass hydrogen gas at a flow rate of 700 mL / min for 2 h to obtain a titanium fiber modified by coating.
[0039] S2. The modified titanium fiber and the water-soluble vinylon fiber with a diameter of 20 μm were mixed at a mass ratio of 8:2, and ultrasonically dispersed in deionized water for 3 hours until uniformly dispersed. Then, the titanium fiber felt was formed by a sheet forming machine to form a titanium fiber felt with uniform thickness. The obtained titanium fiber felt had a weight of 400 g / m 2 ;
[0040] S3. Take 2 layers of the titanium fiber felt prepared in S2, stack them neatly and press them, then put them into a 1000°C vacuum sintering furnace for 4 hours, keep them warm for 2 hours, and finally roll them flat. The thickness of the titanium fiber felt is 0.8 mm.
[0041] Example 4
[0042] S1. Titanium fiber with a diameter of 20 μm and water-soluble vinylon fiber with a diameter of 15 μm were mixed at a mass ratio of 8:2, and ultrasonicated in deionized water for 3 h until uniformly dispersed. Then, the mixture was formed by a sheet forming machine to form a titanium fiber felt with uniform thickness. The obtained titanium fiber felt had a weight of 100 g / m 2 ;
[0043] S2, stacking the four layers of titanium fiber felt obtained in S1 neatly and pressing them, then putting them into a vacuum sintering furnace at 1000°C for 4 hours, keeping them warm for 2 hours, and finally rolling them flat, the thickness of the prepared titanium fiber felt is 0.39 mm;
[0044] S3, the titanium fiber felt in S2 is first cleaned with a methanol solution, then immersed in a 15% oxalic acid solution for 20 minutes, and then repeatedly rinsed with deionized water until the surface of the titanium fiber felt is neutral, and then dried to obtain a titanium fiber felt substrate to be deposited;
[0045] S4. Put 30 mg of ruthenium chloride trihydrate and 20 mg of [bis(2,2,6,6-tetramethyl-3,5-heptanedicarboxylate)(1,5-epoxydiene)ruthenium] into a supercritical device, place the titanium fiber felt substrate to be deposited at the bottom of the device, introduce carbon dioxide gas at a flow rate of 220 mL / min, heat the device to 200°C, and increase the pressure to 16 MPa, so that the precious metal precursor and carbon dioxide in the device reach a critical fluid state, the stirring speed is 100 r / min, and the deposition time is 20 min; then depressurize the device to 5 MPa at 300°C, and introduce hydrogen at a flow rate of 500 mL / min for 2 h; obtain a titanium fiber felt containing ruthenium coating, and the thickness of the titanium fiber felt is 0.4 mm.
[0046] Example 5
[0047] S1. Titanium fiber with a diameter of 18 μm and water-soluble vinylon fiber with a diameter of 15 μm were mixed in a mass ratio of 8:2, and ultrasonicated in deionized water for 3 h until uniformly dispersed. Then, the mixture was formed by a sheet forming machine to form a titanium fiber felt with uniform thickness. The obtained titanium fiber felt had a weight of 50 g / m 2 ;
[0048] S2, stacking 8 layers of titanium fiber felt obtained in S1 neatly and pressing them, then putting them into a vacuum sintering furnace at 1000°C for 4 hours, keeping them warm for 2 hours, and finally rolling them flat. The thickness of the prepared titanium fiber felt is 0.23 mm;
[0049] S3, the titanium fiber felt in S2 is first cleaned with a methanol solution, then immersed in a 20% oxalic acid solution for 20 minutes, and then repeatedly rinsed with deionized water until the surface of the titanium fiber felt is neutral, and then dried to obtain a titanium fiber felt substrate to be deposited;
[0050] S4. Place 30 mg of ruthenium chloride trihydrate, 20 mg of [bis(2,2,6,6-tetramethyl-3,5-heptanedicarboxylic acid)(1,5-epoxydiene)ruthenium] and 10 mg of iridium acetylacetonate into a supercritical device, place the titanium fiber felt substrate to be deposited at the bottom of the device, introduce carbon dioxide gas at a flow rate of 320 mL / min, heat the device to 200°C, and pressurize it to 16 MPa, so that the precious metal precursor and carbon dioxide in the device reach a critical fluid state, the stirring speed is 100 r / min, and the deposition time is 20 min; then depressurize the device to 5 MPa at 300°C, and introduce hydrogen at a flow rate of 500 mL / min for 1.5 h; obtain a titanium fiber felt containing ruthenium coating, the thickness of the titanium fiber felt is 0.25 mm.
[0051] Example 6
[0052] S1. Titanium fiber with a diameter of 50 μm and water-soluble vinylon fiber with a diameter of 20 μm were mixed in a mass ratio of 8:2, and ultrasonicated in deionized water for 3 h until uniformly dispersed. Then, the mixture was formed by a sheet forming machine to form a titanium fiber felt with uniform thickness. The obtained titanium fiber felt had a weight of 500 g / m 2 ;
[0053] S2, stacking the two layers of titanium fiber felt obtained in S1 neatly and pressing them, then putting them into a vacuum sintering furnace at 1000°C for 4 hours, keeping them warm for 2 hours, and finally rolling them flat, the thickness of the prepared titanium fiber felt is 0.9 mm;
[0054] S3, the titanium fiber felt in S2 is first cleaned with a methanol solution, then immersed in a 20% oxalic acid solution for 20 minutes, and then repeatedly rinsed with deionized water until the surface of the titanium fiber felt is neutral, and then dried to obtain a titanium fiber felt substrate to be deposited;
[0055] S4. Put 35 mg of ruthenium chloride trihydrate and 20 mg of [bis(2,2,6,6-tetramethyl-3,5-heptanedicarboxylic acid)(1,5-epoxydiene)ruthenium] into a supercritical device, place the titanium fiber felt substrate to be deposited at the bottom of the device, introduce carbon dioxide gas at a flow rate of 600 mL / min, heat the device to 200°C, and increase the pressure to 18 MPa, so that the precious metal precursor and carbon dioxide in the device reach a critical fluid state, the stirring speed is 180 r / min, and the deposition time is 30 min; at 300°C, the device is depressurized to 5 MPa, and hydrogen is introduced at a flow rate of 500 mL / min for 2 hours; a ruthenium-coated titanium fiber felt is obtained, and the thickness of the titanium fiber felt is 0.93 mm.
[0056] Comparative Example 1
[0057] S1. Titanium fiber with a diameter of 20 μm and water-soluble vinylon fiber with a diameter of 15 μm were mixed in a mass ratio of 8:2, and ultrasonically dispersed in deionized water for 3 hours until uniformly dispersed. Then, the mixture was formed by a sheet forming machine to form a titanium fiber felt with uniform thickness. The obtained titanium fiber felt had a quantitative value of 100 g / m 2 ;
[0058] S2, stacking the four layers of titanium fiber felt prepared in S1 neatly and pressing them, then putting them into a vacuum sintering furnace at 1000°C for 4 hours, keeping them warm for 2 hours and then rolling them flat, the thickness of the titanium fiber felt prepared is 0.39 mm;
[0059] S3, the titanium fiber felt in S2 is first cleaned with a methanol solution, then immersed in a 15% oxalic acid solution for 20 minutes, and then repeatedly rinsed with deionized water until the surface of the titanium fiber felt is neutral, and finally dried to obtain a titanium fiber felt substrate to be deposited;
[0060] S4. Take 2g of phenolic resin and 1g of dispersant and completely dissolve them in 30g of isopropanol, then add 35g of iridium powder and disperse them evenly by ultrasonication to obtain a conductive metal slurry; apply the conductive metal slurry onto the titanium fiber felt substrate to be deposited in S3, and then dry it in an oven at 120°C for 1h to obtain a titanium fiber felt containing an iridium coating, the thickness of the titanium fiber felt being 0.4mm.
[0061] The resistivity of the anode gas transport layer prepared in Examples 1-6 and Comparative Example 1 and the polarization curve after assembling the electrolytic cell were tested.
[0062] pass Figure 1 It can be seen from the data that the resistivity of the anode gas transport layer prepared in Examples 1-6 is lower than that in Comparative Example 1 at the same pressure, indicating that the titanium fiber felt prepared by the method of the present invention has a higher conductivity.
[0063] according to Figure 2 The data show that the anode gas transport layer prepared in Examples 1-6 has a flow rate of 2000 A / cm 2 The electrolysis voltage when the operating current is dense is significantly lower than that of Comparative Example 1, indicating that the titanium fiber felt prepared by the present invention has higher catalytic activity.
[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for modifying a titanium-based porous transport layer using supercritical fluid technology, characterized in that: The following steps are performed in sequence: S11. Put the precursor of the precious metal into a supercritical device, put the titanium fiber at the bottom of the device, and introduce carbon dioxide gas into the sealed container at a gas flow rate of 220-520 mL / min. While keeping the carbon dioxide gas flowing, heat the supercritical device to a temperature of 200-400°C and a pressure of 15-18 MPa according to the program, so that the precursor of the precious metal and the carbon dioxide in the device reach a supercritical fluid state. Maintain magnetic stirring during the entire heating process at a stirring speed of 100-200 r / min to make the deposition more uniform, wherein the deposition time is 20-30 min. After the deposition is completed, the pressure is released to 5 MPa, and hydrogen is introduced at a gas flow rate of 500-700 mL / min. The temperature of the pressure release process is 300°C and the time is 2 h. After the pressure release is completed, titanium fiber modified by coating is obtained; S12, the titanium fiber modified by plating and the water-soluble vinylon fiber are mixed in a mass ratio of (8-9): (1-2), and ultrasonically treated in deionized water for 3 hours until the dispersion is uniform, and then formed by a sheet forming machine to form a titanium fiber felt with uniform thickness, wherein the titanium fiber felt has a quantitative value of 50-400 g / m 2 ; S13, the titanium fiber felt in step S12 is laminated and pressed, and then placed in a vacuum sintering furnace at 1000°C for 4 hours to remove impurities and part of the adhesive components in the production process, and the heat preservation time is 2 hours. Finally, the titanium fiber felt is rolled and flattened. The thickness of the prepared titanium fiber felt is 0.2-0.8 mm.
2. The method for modifying a titanium-based porous transport layer using supercritical fluid technology according to claim 1, characterized in that: In step S11, the precursor of the precious metal is one or more of ruthenium chloride trihydrate, [bis(2,2,6,6-tetramethyl-3,5-heptanedioate)(1,5-epoxydiene)ruthenium], and iridium acetylacetonate.
3. The method for modifying a titanium-based porous transport layer using supercritical fluid technology according to claim 1, characterized in that: In step S11, the diameter of the titanium fiber is 18-50 μm.
4. The method for modifying a titanium-based porous transport layer using supercritical fluid technology according to claim 1, characterized in that: In step S12, the diameter of the water-soluble vinylon fiber is 7 to 20 μm.
5. A method for modifying a titanium-based porous transport layer using supercritical fluid technology, characterized in that: The following steps are performed in sequence: S51. Mix titanium fiber and water-soluble vinylon fiber in a mass ratio of 8:2, put them into deionized water for 3 hours for ultrasonication until they are evenly dispersed, and then form them into titanium fiber felt with uniform thickness through a sheet forming machine. The obtained titanium fiber felt has a weight of 50 to 500 g / m 2 ; S52, laminating and pressing the titanium fiber felt obtained in S51, and then sintering it in a vacuum sintering furnace at 1000° C. for 4 hours, keeping it warm for 2 hours, and finally rolling and leveling it. The thickness of the prepared titanium fiber felt is 0.23 to 0.90 mm; S53, the titanium fiber felt in S52 is first cleaned with a methanol solution, then immersed in an oxalic acid solution with a mass fraction of 15-20% for 20 minutes, and then repeatedly rinsed with deionized water until the surface of the titanium fiber felt is neutral, and then dried to obtain a titanium fiber felt matrix to be deposited; S54. Place the precious metal precursor into a supercritical device, place the titanium fiber felt substrate to be deposited at the bottom of the device, introduce carbon dioxide gas at a flow rate of 220-600 mL / min, heat the device to 200°C, and increase the pressure to 16-18 MPa, so that the precious metal precursor and carbon dioxide in the device reach a critical fluid state. The stirring speed is 100-180 r / min, and the deposition time is 20-30 min. Then, the device is depressurized to 5 MPa, and hydrogen is introduced at a flow rate of 500 mL / min for 2 h at 300°C to obtain a ruthenium-coated titanium fiber felt with a thickness of 0.25-0.93 mm.
6. The method for modifying a titanium-based porous transport layer using supercritical fluid technology according to claim 5, characterized in that: In step S51, the diameter of the titanium fiber is 18 to 50 μm, and the diameter of the water-soluble vinylon fiber is 15 to 20 μm.
7. The method for modifying a titanium-based porous transport layer using supercritical fluid technology according to claim 5, characterized in that: In step S54, the precursor of the precious metal is one or more of ruthenium chloride trihydrate, [bis(2,2,6,6-tetramethyl-3,5-heptanedioate)(1,5-epoxydiene)ruthenium], and iridium acetylacetonate.
Citation Information
Patent Citations
Preparation method of zirconium oxide fiber reinforced high-temperature-resistant block aluminum oxide aerogel
CN117069431A
Iridium-platinum catalyst for PEM electrolyzed water and preparation method thereof
CN117403271A
Catalyst preparation using supercritical solvent
US4916108A